2009
DOI: 10.1002/jcp.21735
|View full text |Cite
|
Sign up to set email alerts
|

Survival responses of human embryonic stem cells to DNA damage

Abstract: Pluripotent human embryonic stem (hES) cells require mechanisms to maintain genomic integrity in response to DNA damage that could compromise competency for lineage-commitment, development and tissue-renewal. The mechanisms that protect the genome in rapidly proliferating hES cells are minimally understood. Human ES cells have an abbreviated cell cycle with a very brief G1 period suggesting that mechanisms mediating responsiveness to DNA damage may deviate from those in somatic cells. Here, we investigated how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
136
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(151 citation statements)
references
References 24 publications
13
136
1
1
Order By: Relevance
“…In principle, a lack of damage-induced checkpoint at the G1=S boundary would limit the time and resources available for DNA damage repair and compromise genomic integrity. However, mammalian ESC exhibit the robust induction of a DNA damage response that facilitates the elimination of damaged cells by apoptosis [4,37,44,50]. Consistent with previous reports [43], our results demonstrate that DNA damage response mechanisms in mESC include the recruitment of DNA repair components and the activation of gH2AX foci.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In principle, a lack of damage-induced checkpoint at the G1=S boundary would limit the time and resources available for DNA damage repair and compromise genomic integrity. However, mammalian ESC exhibit the robust induction of a DNA damage response that facilitates the elimination of damaged cells by apoptosis [4,37,44,50]. Consistent with previous reports [43], our results demonstrate that DNA damage response mechanisms in mESC include the recruitment of DNA repair components and the activation of gH2AX foci.…”
Section: Discussionsupporting
confidence: 88%
“…In these cells, the coordination of DNA damagesensing proteins and mediators of DNA damage check points would promote cell cycle arrest and allow the completion of HR before the cell enters G2 [49]. After externally induced DNA damage, and in common with teratocarcinoma cells, human and murine ESC traverse G1-phase progresses through S-phase and accumulate in at the G2=M boundary [4,37,44,50]. In principle, a lack of damage-induced checkpoint at the G1=S boundary would limit the time and resources available for DNA damage repair and compromise genomic integrity.…”
Section: Discussionmentioning
confidence: 99%
“…The function of p53-p21 axis has been studied by several groups in both mouse and human ESCs and in pluripotent human embryonal carcinoma cells using various strategies [10,[29][30][31][32]. Surprisingly, there have been many discrepancies between their findings, including differences in the ability of cells to transactivate the p21 gene or to produce increased levels of p21 protein when p21 transcripts are upregulated [10,[29][30][31]33]. When we examined p53 expression in hESCs with UVC-induced G1 delay, we found that at 3 hours after UVC irradiation, p53 protein is already dramatically increased, is phosphorylated on serines 15, 33, and 392, and localizes completely to cell nuclei.…”
Section: For the Experimental Design) (D-f)mentioning
confidence: 99%
“…Surprisingly, several studies have recently reported that hESCs fail to fully execute the G1/S checkpoint, which may account for the fast mitogenindependent (''automated'') progression of hESCs through G1 [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Filion et al came to this conclusion as they did not observe increases in G1-phase cells after treatment of hES cells with -irradiation. They did, however, observe G2-arrest, indicating that G2/M checkpoint is functional (Filion et al 2009). In agreement with this, Sokolov et al observed a G2-arrest, but no G1-arrest after treatment of hES cells with 1Gy dose of X-rays (Sokolov et al 2011).…”
Section: Box 2: Human Embryonic Stem Cells and Induced Pluripotent Stmentioning
confidence: 99%